Pengaruh Digital Marketing dan Kualitas Pelayanan terhadap Minat Beli pada Matahari Department Store di Masa Pandemi Covid-19 - Karimah, Rima Latiefah; Widhiastuti, Dheas Asteria; Arlini, Lida (Fakultas Ekonomi dan Bisnis, 2022)
Fashion is one of the secondary needs of society, and even fashion has become a trend for men and women worldwide. Matahari Department Store is one of the places that sell fashion products and well known as retail company. It realized that there is currently a Covid 19 pandemic, which causes all sectors to experience an imbalance, including Matahari Department Store. The company is experiencing income instability and because of that several store branches are closed. This study aims to determine and analyze the effect of Digital Marketing and Service Quality on Buying Interest at Matahari Department Store Karawang. Analysis of the data used in this study is multiple linear regression analysis with verification and descriptive approach with the number of samples used as many as 101 respondents. The results indicate that Digital Marketing (X1) has a partial effect on Purchase Intention of 3,744 and a partial effect of Service Quality (X2) on Purchase Interest of 7,580. In contrast, the results of the simultaneous test of Digital Marketing and Service Quality significantly influence Buying Interest. The calculated F obtained is 88.406 > 2.37. So it can be concluded that better digital marketing and service quality will increase buyer interest.